Immune and Neuroendocrine Trait and State Markers in Psychotic Illness: Decreased Kynurenines Marking Psychotic Exacerbations - De Picker, Livia; Fransen, Erik; Coppens, Violette; Timmers, Maarten; de Boer, Peter; Oberacher, Herbert; Fuchs, Dietmar; Verkerk, Robert; Sabbe, Bernard; Morrens, Manuel (Frontiers in Immunology, 2020)
Objective: Different patterns of immune system upregulation are present in the acute versus post-treatment states of psychotic illness. We explored the existence of state and trait markers in the peripheral immune system and two immune-associated neuroendocrine pathways (IDO and GTP-CH1 pathway) in a longitudinal sample of psychosis patients. We also evaluated the association of these markers with neuropsychiatric symptomatology. Method: Plasma concentrations of peripheral blood markers were measured in a transdiagnostic group of 49 inpatients with acute psychosis and 52 matched healthy control subjects. Samples were obtained in patients within 48 hours after hospital admission for an acute psychotic episode (before initiation of antipsychotics), after 1-2 weeks and again after 8 weeks of treatment. Kynurenine, kynurenic acid (KA), 3-hydroxykynurenine (3-HK), quinolinic acid (QA), phenylalanine, tyrosine, nitrite and neopterin were measured using HPLC and LC-MS/MS analysis. Concentrations of CRP, CCL2 (MCP1) and cytokines were determined with multiplex immunoassay. PANSS interviews and cognitive tests were performed at baseline and follow-up. Mixed model analyses were used to identify trait and state markers. Results: Patients had significantly higher plasma concentrations of CRP, CCL2, IL1RA and lower concentrations of KA and KA/Kyn at all time points (F7.5-17.5, all p<.001). Increased concentrations of IL6, IL8, IL1RA, TNFα and CCL2 and decreased QA and 3-HK (F8.7-21.0, all p<.005) were found in the acute psychotic state and normalized after treatment. Low nitrite concentrations at admission rose sharply after initiation of antipsychotic medication (F42.4, p<.001). PANSS positive scale scores during the acute episode correlated with pro-inflammatory immune markers (r≥|0.5|), while negative scale scores correlated inversely with IDO pathway markers (r≥|0.4|). Normalization of KA and 3-HK levels between admission and follow-up corresponded to a larger improvement of negative symptoms (r0.5, p<.030) A reverse association was found between relative improvement of SDST scores and decreasing KA levels (r0.5, p.010). Conclusion: The acute psychotic state is marked by state-specific increases of immune markers and decreases in peripheral IDO pathway markers. Increased CRP, CCL2 and IL1RA, and decreased KA and KA/Kyn are trait markers of psychotic illness.